2020
DOI: 10.1103/physrevb.102.161115
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dirac fermions in the intrinsic antiferromagnetic topological insulators (MnBi2Te4)(Bi2Te3

Abstract: Topological surface states with intrinsic magnetic ordering in the MnBi2Te4(Bi2Te3)n compounds have been predicted to host rich topological phenomena including quantized anomalous Hall effect and axion insulator state. Here we use scanning tunneling microscopy to image the surface Dirac fermions in MnBi2Te4 and MnBi4Te7. We have determined the energy dispersion and helical spin texture of the surface states through quasiparticle interference patterns far above Dirac energy, which confirms its topological natur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 55 publications
4
10
0
Order By: Relevance
“…Therefore the type A defects can be identified with the Bi Te antisites, similarly to what happens in Bi 2 Te 3 TI 63 , where they also appear as bright protrusions for both bias polarities. This conclusion is in line with previous STM studies of MnBi 2 Te 4 (0001) 13,61,62,64 .…”
Section: Figure 1dsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore the type A defects can be identified with the Bi Te antisites, similarly to what happens in Bi 2 Te 3 TI 63 , where they also appear as bright protrusions for both bias polarities. This conclusion is in line with previous STM studies of MnBi 2 Te 4 (0001) 13,61,62,64 .…”
Section: Figure 1dsupporting
confidence: 93%
“…Thus, we attribute the triangular-shaped depressions to the Mn Bi substitutions in the subsurface layer. Similar features have been previously observed in STM for magnetically doped Bi 2 Se 3 -family TIs [58][59][60] and, recently, for MnBi 2 Te 4 (0001) 13,61,62 . Besides, the existence of Mn Bi defects has also been claimed recently based on the electron energy loss spectroscopy and transmission electron microscopy analysis 55 .…”
Section: Figure 1dsupporting
confidence: 87%
See 1 more Smart Citation
“…For φ = 0.5 and TG = 410 °C, the surface showed randomly oriented elongated structures, which might be due to the formation of a Mn-rich phase; its rms roughness was 3.85 nm. The STM result revealed that the hexagonal atomic structure on the surface is consistent with the imaging of the topmost Te layer [46,47]; the in-plane lattice parameter was 4.0 Å, as shown in Figure 2f. These structural features confirmed by the AFM and XRD reveal the high quality of the pure MnBi2Te4 films grown by the delicate MBE method.…”
Section: Surface Morphologysupporting
confidence: 71%
“…The layering step is distinguishable on the enlarged surface shown in Figure 2e. The step height is ~1.4 nm (inset of Figure 2e), which is the same as the height of a single SL of MnBi2Te4 [25,46]. For φ = 0.5 and TG = 410 °C, the surface showed randomly oriented elongated structures, which might be due to the formation of a Mn-rich phase; its rms roughness was 3.85 nm.…”
Section: Surface Morphologymentioning
confidence: 64%